2017
DOI: 10.1103/physrevd.96.106006
|View full text |Cite
|
Sign up to set email alerts
|

Exact time dependence of causal correlations and nonequilibrium density matrices in holographic systems

Abstract: We present the first exact calculations of the time dependence of causal correlations in driven nonequilibrium states in (2 + 1)-dimensional systems using holography. Comparing exact results with those obtained from simple prototype geometries that are parametrized only by a time dependent temperature, we find that the universal slowly varying features are controlled just by the pump duration and the initial and final temperatures only. We provide numerical evidence that the locations of the event and apparent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…We emphasize that this is not the most general bulk solution for a global quench, and that the details may depend on the specific source that is turned on. However, there is strong numerical and analytic evidence to support the idea that even simple models such as AdS-Vaidya already capture the relevant universal features of the time-evolution and subsequent thermalization after a global quench [35,[77][78][79][80][81]. For example, in the recent paper [81] it was found that the gross features of the correlations following the quench are controlled by just a few parameters: the pump duration and the initial and final temperatures, which are all tuneable in (2.10).…”
Section: Entanglement Entropy After Global Quenchesmentioning
confidence: 99%
“…We emphasize that this is not the most general bulk solution for a global quench, and that the details may depend on the specific source that is turned on. However, there is strong numerical and analytic evidence to support the idea that even simple models such as AdS-Vaidya already capture the relevant universal features of the time-evolution and subsequent thermalization after a global quench [35,[77][78][79][80][81]. For example, in the recent paper [81] it was found that the gross features of the correlations following the quench are controlled by just a few parameters: the pump duration and the initial and final temperatures, which are all tuneable in (2.10).…”
Section: Entanglement Entropy After Global Quenchesmentioning
confidence: 99%
“…See[44] for the non-equilibrium retarded correlation function in a hydrodynamic expansion, and[45,46] for AdS-Vaidya and states corresponding to quenches, etc. The latter uses the prescription of[10].…”
mentioning
confidence: 99%